Assessment of musculoskeletal problems among desk job employees of a tertiary care hospital in Goa - Mendes, Jennifer; Shah, Hemangini K. (International Journal Of Community Medicine And Public Health, 2021)
Background: Musculoskeletal disorders (MSDs) are a leading cause of disability and the most frequent cause of all health-related absence from work. There is lack of information about MSDs among desk job employees. Methods: A cross sectional study, carried out among desk job employees engaged in administrative work at a tertiary care hospital in Goa involved, data collection on MSDs using Standardised Nordic Musculoskeletal Questionnaire (NMQ) and workstation ergonomics assessment using NIH (National Institute of Health) checklist. Results: Among 110 respondents, 50 males and 60 females, majority (42.7%) were from age group 31-40 years. As per the NMQ, one-year prevalence of MSDs was highest in lower back (55.5%), followed by neck (48.2%); and the lowest in ankles (4.5%). Regular postural breaks were not taken by 59 (53.6%) of the total participants, of which 41(37.3%) complained of at least one MSD and the association was statistically significant (p=0.001). On ergonomic assessment, 62 (56.4%) had chairs with poor lower back support, of which 44 (40%) complained of lower backache; 20 (18.2%) were uncomfortable during keyboard use and 18 (16.4%) with desk setup. Of the 40 participants with continuous computer use for 4-5 hours, 27 complained of neck pain and there was a significant association found between continuous computer use and neck pain (p=0.003). Conclusions: Based on the findings, ergonomic training workshops should be conducted, and the workstation design needs to be improved to reduce the burden of work-related MSDs.